Multimodality Cardiovascular Imaging of Hyperthrophic Cardiomyopathy : A Review Article - Ardian Rizal; Novi Kurnianingsih; Anna Fuji Rahimah; Veny Kurniawati; Mohammad Saifur Rohman (Heart Science Journal, 2020)
AbstractThe most common genetic cardiomyopathy, HCM has a prevalence about 0.2%. It is transmitted autosomal dominant inheritance pattern. The natural history is benign but adverse outcomes can be happened in some patients including sudden cardiac death, symptoms secondary to dynamic left ventricular outflow tract (LVOT) obstruction, diastolic filling abnormalities, atrial fibrillation, and LV systolic dysfunction.Imaging modalities can be used to evaluate cardiac structure and function, the presence and severity of dynamic obstruction, mitral valve abnormalities, mitral regurgitation, as well as myocardial ischemia and fibrosis. Echocardiography is the initial imaging modality for evaluation of cardiac structure. CMR is recommended when echocardiographic images is not adequate in selected patients with high index of suspicion for HCM. In case of contraindication to CMR, patients with ICDs or pacemakers, Cardiac CT is recommended. Imaging can be used to guide treatment, screening and preclinical diagnosis in patient HCM.